Method for preparing carbon nanotube / metal matrix composite material assisted by ultrasonic wet method
Through the ultrasonic dampness method, the carbon nanotubal pipe is evenly dispersed in the metal matrix, which solves the problem of difficulty even dispersing and damaging the structure integrity in existing technologies. preparation.
Patent Information
- Application Number
- CN202310127131.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-14
AI Technical Summary
The prior art is difficult to evenly disperse carbon nanotubes in aluminum-based materials, and forced dispersion of high-energy ball milling and plastic deformation methods lead to damage to the structural and morphological integrity of carbon nanotubes, reducing its improvement in the mechanical properties of metal-based composite materials. Amplitude.
The ultrasonic wetting method is adopted, and the carbon nanopot can be arranged uniformly in the metal matrix through the premise that the high -frequency ultrasonic energy wetting method is to greatly disperse the carbon nanoma structure and morphological integrity. Specific steps include preparing carbon nanotuba water solution, preparing sliced metal powder, and carbon nanotubes to adsorb in chip -shaped metal powder, and obtain high -performance composite materials through sintering and density treatment.
The uniform dispersing of the carbon nanotubes in the metal matrix has greatly retained the shape and structure of the carbon nanoma, which greatly improves the mechanical properties of the carbon nanotuba/metal substrate composite material.
Smart Images

Figure CN116103560B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a method for preparing a carbon nanotube / metal matrix composite material by using an ultrasonic wet process as an auxiliary. Background Art
[0002] Carbon nanotubes (CNTs) are a type of circular tube with a spiral structure composed of carbon atoms. They are currently the hardest and strongest synthetic carbon materials. They are ideal nano-reinforced materials for composite materials because of their quasi-one-dimensional carbon structure with a large aspect ratio, unique and superior mechanical, thermal and electrical properties, and light weight. The combination of metal materials (pure metals or alloys) and carbon nanotubes can produce nano-composites with a wide range of application potentials.
[0003] The current mainstream method for preparing carbon nanotube / metal matrix composite materials is powder metallurgy. Taking aluminum matrix as an example, one of the most critical steps is to make carbon nanotubes evenly dispersed in the initial aluminum powder, which has an important influence on the final distribution of carbon nanotubes in carbon nanotube / aluminum composite materials. However, to date, whether through dry powder mixing or wet slurry mixing, the goal of uniform distribution of carbon nanotubes in aluminum powder has not been achieved, and the ideal strengthening effect cannot be achieved. The reasons are as follows: 1. The initial aluminum powder is a spherical particle with a diameter of tens of microns. This structure represents its large curvature, strong surface hydrophobicity and small surface area, while carbon nanotubes are typical nanofibers with a diameter of tens of nanometers, showing a considerable surface area and hydrophilic surface. Therefore, simple wet slurry mixing cannot make carbon nanotubes and aluminum powder closely combined; 2. The typical long fiber structure of carbon nanotubes is more prone to agglomeration, and carbon nanotube clusters are entangled and cannot be evenly dispersed in the initial aluminum powder.
[0004] At present, the high-energy ball milling method and plastic deformation method commonly used in dry powder mixing can disperse carbon nanotubes relatively evenly, but the violent friction damages the structure of carbon nanotubes, reducing the strengthening performance of carbon nanotubes on the final aluminum-based composite material. For example, Chinese patent CN103614672A discloses a method for preparing a carbon nanotube-reinforced aluminum-based composite material, which is prepared by high-energy ball milling. In essence, it still belongs to the mixing between solids, and the uniformity of CNT distribution cannot be guaranteed. In addition, the CNT is embedded in the aluminum powder particles by ball milling, which greatly damages the integrity of the CNT structure and morphology, affecting the mechanical properties of the final composite material. Summary of the invention
[0005] The technical problem to be solved by the present invention is that in view of the two problems that the above-mentioned prior art has the difficulty in uniformly dispersing carbon nanotubes in aluminum-based materials, and the forced dispersion by high-energy ball milling and plastic deformation methods leads to damage of the structural and morphological integrity of the carbon nanotubes, which ultimately reduces the extent to which the carbon nanotubes improve the mechanical properties of metal-based composites. A method for preparing carbon nanotube / metal matrix composite materials assisted by ultrasonic wet method is provided. Through the assistance of high-frequency ultrasonic energy wet method, the carbon nanotubes in the metal matrix are uniformly dispersed and arranged while greatly ensuring the structural and morphological integrity of the carbon nanotubes, so as to finally obtain a carbon nanotube / metal matrix composite material with uniform structure and greatly improved performance.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is:
[0007] A method for preparing a carbon nanotube / metal matrix composite material assisted by an ultrasonic wet process comprises the following steps:
[0008] S1. preparing a carbon nanotube aqueous solution: dispersing carbon nanotubes in an amphoteric surfactant and stirring to prepare a carbon nanotube active agent solution, introducing the carbon nanotube active agent solution into distilled water in an experimental container, and using ultrasonic vibration to evenly disperse the carbon nanotubes to obtain an ink-like carbon nanotube suspension;
[0009] S2, preparing flaky metal powder: ordinary metal powder is put into an anti-cold welding solvent and mixed, and then flaky metal powder slurry is obtained by ball milling, and the slurry is filtered and dried to obtain flaky metal powder;
[0010] S3, carbon nanotubes adsorbed on flaky metal powder: slowly adding flaky metal powder into the carbon nanotube suspension, and simultaneously starting an ultrasonic device to longitudinally vibrate the carbon nanotube suspension until the color of the suspension changes from black to transparent, and after filtering, a carbon nanotube / metal-based composite powder with uniformly distributed carbon nanotubes can be obtained;
[0011] S4. Carbon nanotube / metal matrix composite powder consolidation: The carbon nanotube / metal matrix composite powder is sintered and densified to obtain a high-performance carbon nanotube / metal matrix composite mother material.
[0012] In the above method, in step S3, the ratio of the length of the ultrasonic impact head immersed in the liquid surface to the total height of the carbon nanotube suspension is 1:10 to 1:4, the ultrasonic frequency range is 20kHz to 60kHz, and the shape of the top of the ultrasonic impact head is consistent with the shape of the liquid surface of the experimental container.
[0013] In the above method, in step S1, the type of the amphoteric surfactant is any one of lecithin, amino acid type, betaine type, or a combination of two or more thereof.
[0014] In the above method, in step S1, the weight percentage of carbon nanotubes in the carbon nanotube active agent solution is 0.01% to 20%.
[0015] In the above method, in step S1, the frequency of the ultrasonic vibration is 2kHz to 60kHz.
[0016] In the above method, in step S2, the anti-cold welding solvent is a solvent that can prevent metal powder from cold welding, which is composed of 1.5wt% stearic acid and 2L ethanol.
[0017] In the above method, in step S2, the ball milling conditions are a rotation speed of 400 to 900 rpm, a ball milling time of 2 to 10 hours, a ball-to-material ratio of 5 to 25:1, and water cooling for 2 to 3 hours.
[0018] In the above method, the metal matrix is iron-based, nickel-based, copper-based, aluminum-based, magnesium-based or silver-based.
[0019] The beneficial effects of the present invention are:
[0020] 1. The method of the present invention is assisted by high-frequency ultrasonic energy wet method, and the carbon nanotubes in the metal matrix are evenly dispersed under the premise of greatly ensuring the structural and morphological integrity of the carbon nanotubes, so as to finally obtain a carbon nanotube / metal matrix composite material with uniform structure and greatly improved performance. Specifically, the ultrasonic vibration energy drives the CNT, metal powder, and solvent to make a circular motion in the longitudinal direction, increasing the contact rate between the CNT and the metal powder and the random distribution rate of the CNT; in addition, the ultrasonic vibration suspension can generate a large number of cavitation bubbles, which carry a certain amount of energy to impact the suspended CNT, causing it to be impacted to the surface of the metal powder, achieving the effect of mechanical embedding and improving the adsorption rate. At the same time, due to the small energy and high frequency of the cavitation bubbles, the damage to the CNT structure can be ignored, and a certain impact efficiency is guaranteed.
[0021] 2. In step S1 of the method of the present invention, ultrasonic impact is used to longitudinally vibrate the CNT suspension. Ultrasonic impact is to convert high-frequency oscillating electrical signals into ultrasonic waves of longitudinal mechanical vibration. The ultrasonic vibration energy drives the CNT and water flow to perform circular motion in the longitudinal direction to avoid entanglement of CNT clusters. Compared with ordinary stirring methods, its dispersion efficiency is higher and the CNT distribution is more uniform. The amphoteric surfactant is mixed in advance to make the CNT easier to adsorb on the metal powder later.
[0022] 3. In step S2, the method of the present invention utilizes ball milling to grind conventional granular metal powder into flakes, which greatly increases the surface area available for CNT adsorption, while reducing the curvature and surface hydrophobicity of the metal powder, making it easier to adsorb suspended CNTs in step S3, further improving the subsequent uniform dispersion of carbon nanotubes in the metal matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0024] Figure 1 It is a schematic flow diagram of the method of the present invention;
[0025] Figure 2 Schematic diagram of the ultrasonic wet method assisted preparation of carbon nanotube suspension in step S1 of the method of the present invention;
[0026] Figure 3 This is a schematic diagram of the ultrasonic wet method assisted preparation of carbon nanotube / metal matrix composite powder slurry in step S3 of the method of the present invention.
[0027] In the figure: 1. Ultrasonic impact head; 2. Experimental container; 3. Carbon nanotubes; 4. Carbon nanotube / metal matrix composite powder. DETAILED DESCRIPTION
[0028] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0029] like Figure 1 As shown, a method for preparing a carbon nanotube / metal matrix composite material assisted by an ultrasonic wet process according to an embodiment of the present invention comprises the following steps:
[0030] S1. Prepare a carbon nanotube aqueous solution: disperse carbon nanotubes in an amphoteric surfactant and stir to prepare a carbon nanotube active agent solution, introduce the carbon nanotube active agent solution into the distilled water in the experimental container 2 (to prevent the carbon nanotubes from being entangled and unable to be evenly dispersed due to the attraction of ionic impurities in the water), and use ultrasonic longitudinal (i.e., liquid depth direction) vibration to evenly disperse the carbon nanotubes 3 to obtain an ink-like carbon nanotube suspension. Figure 2 , the ultrasonic impact head 1 extends 2 cm below the liquid surface of the solution; the ultrasonic frequency is 2kHz to 60kHz, and 10kHz is used in this embodiment; the shape of the top of the ultrasonic impact head 1 is consistent with the shape of the liquid surface of the experimental container 2. The type of amphoteric surfactant is any one of lecithin, amino acid type, and betaine type, or a combination of two or more. The weight percentage of carbon nanotubes in the carbon nanotube active agent solution is 0.01% to 20%.
[0031] S2. Preparation of flaky metal powder: ordinary 1-100 μm metal powder is mixed in a cold welding prevention solvent, and then a flaky metal powder slurry is obtained by high-energy ball milling. The slurry is filtered and dried to obtain flaky metal powder of the same size. The cold welding prevention solvent is a solvent composed of 1.5wt% stearic acid and 2L ethanol that can prevent cold welding of metal powder. The ball milling conditions are a rotation speed of 400-900rpm, a ball milling time of 2-10h, a ball-to-material ratio of 5-25:1, and water cooling for 2-3h.
[0032] S3. Carbon nanotubes adsorbed on flaky metal powder: Slowly add flaky metal powder into the carbon nanotube suspension, and start the ultrasonic device to longitudinally vibrate the carbon nanotube suspension until the color of the suspension changes from black to transparent. After filtering, carbon nanotube / metal matrix composite powder with uniformly distributed carbon nanotubes can be obtained. See Figure 3 The ratio of the length of the ultrasonic impact head 1 immersed under the liquid surface to the total height of the carbon nanotube suspension is 1:10 to 1:4. In this embodiment, it extends 2 cm below the liquid surface of the solution. The ultrasonic frequency range is 20 kHz to 60 kHz, and 40 kHz is used in this embodiment.
[0033] S4. Carbon nanotube / metal matrix composite powder consolidation: The carbon nanotube / metal matrix composite powder is sintered and densified to obtain a high-performance carbon nanotube / metal matrix composite mother material.
[0034] The metal substrates applicable to the method of the present invention include iron-based, nickel-based, copper-based, aluminum-based, magnesium-based, silver-based, etc. It should be noted that: Figure 1 The steps of the method of the present invention are illustrated by taking an aluminum base as a specific embodiment.
[0035] In step S1 of the method of the present invention, ultrasonic impact is used to longitudinally vibrate the CNT suspension. Ultrasonic impact is an ultrasonic wave that converts a high-frequency oscillating electrical signal into a longitudinal mechanical vibration. The ultrasonic vibration energy drives the CNT and the water flow to perform a cyclic motion in the longitudinal direction to avoid the entanglement of the CNT clusters. Compared with the ordinary stirring method, its dispersion efficiency is higher and the CNT distribution is more uniform; the amphoteric surfactant is mixed in advance to make the subsequent CNT easier to adsorb on the metal powder. In step S2, flaky metal powder is used, which greatly increases the CNT adsorbable surface area compared to the granular metal powder used in the ordinary method, while reducing the curvature and surface hydrophobicity of the metal powder, making it easier to adsorb the suspended CNT in step S3. In step S3, ultrasonic impact is still used to longitudinally vibrate CNT and metal powder suspension, which has the advantages similar to step S1. The ultrasonic vibration energy can be used to promote CNT, metal powder, and solvent to do cyclic motion in the longitudinal direction, thereby increasing the contact rate between CNT and metal powder and the random distribution rate of CNT; in addition, the ultrasonic vibration suspension can generate a large number of cavitation bubbles, which carry a certain amount of energy to impact the suspended CNT, so that it is impacted to the surface of the metal powder, achieving the effect of mechanical embedding and improving the adsorption rate. At the same time, due to the small energy and high frequency of the cavitation bubbles, the damage to the CNT structure can be ignored, and a certain impact efficiency is guaranteed. After sintering and densification treatment after step S4, a carbon nanotube / metal matrix composite material with more uniform CNT dispersion can be obtained. Compared with the carbon nanotube / metal matrix composite material prepared by the conventional method, its mechanical properties can be greatly improved. The main reasons for the improvement are as follows: first, the carbon nanotubes can be dispersed more evenly in the metal matrix; second, the morphology and structure of the carbon nanotubes are retained to the greatest extent. The above two points enable carbon nanotubes to be used as a reinforcing phase to optimize the performance of the composite material.
[0036] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing a carbon nanotube / metal matrix composite material assisted by ultrasonic wet method, characterized in that: The following steps are involved: S1. preparing a carbon nanotube aqueous solution: dispersing carbon nanotubes in an amphoteric surfactant and stirring to prepare a carbon nanotube active agent solution, introducing the carbon nanotube active agent solution into distilled water in an experimental container, and using ultrasonic vibration to evenly disperse the carbon nanotubes to obtain an ink-like carbon nanotube suspension; S2, preparing flaky metal powder: ordinary metal powder is put into an anti-cold welding solvent and mixed, and then flaky metal powder slurry is obtained by ball milling, and the slurry is filtered and dried to obtain flaky metal powder; S3, carbon nanotubes adsorbed on flaky metal powder: slowly adding flaky metal powder into the carbon nanotube suspension, and simultaneously starting an ultrasonic device to longitudinally vibrate the carbon nanotube suspension until the color of the suspension changes from black to transparent, and after filtering, a carbon nanotube / metal-based composite powder with uniformly distributed carbon nanotubes can be obtained; S4. Carbon nanotube / metal matrix composite powder consolidation: The carbon nanotube / metal matrix composite powder is sintered and densified to obtain a high-performance carbon nanotube / metal matrix composite mother material.
2. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S3, the ratio of the length of the ultrasonic impact head immersed in the liquid surface to the total height of the carbon nanotube suspension is 1:10 to 1:4, the ultrasonic frequency range is 20kHz to 60kHz, and the shape of the top of the ultrasonic impact head is consistent with the shape of the liquid surface of the experimental container.
3. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S1, the amphoteric surfactant type is any one of lecithin, amino acid type, betaine type, or a combination of two or more.
4. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S1, the weight percentage of carbon nanotubes in the carbon nanotube active agent solution is 0.01% to 20%.
5. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S1, the frequency of the ultrasonic vibration is 2 kHz to 60 kHz.
6. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S2, the anti-cold welding solvent is a solvent that can prevent metal powder from cold welding, which is composed of 1.5wt% stearic acid and 2L ethanol.
7. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: In step S2, the ball milling conditions are a rotation speed of 400 to 900 rpm, a ball milling time of 2 to 10 hours, a ball-to-material ratio of 5 to 25:1, and water cooling for 2 to 3 hours.
8. The method for preparing carbon nanotube / metal matrix composite material by ultrasonic wet process assisted according to claim 1, characterized in that: The metal matrix is iron-based, nickel-based, copper-based, aluminum-based, magnesium-based or silver-based.
Citation Information
Patent Citations
Preparation method of carbon nano tube-reinforced aluminum base composite material
CN103614672A
Preparation method of micro-nano lamination metal base composite material
CN101817084A
Preparation method for reinforced titanium matrix composite of three-dimensional network-shaped carbon nanotube
CN103526136A